A space-time analysis of mortality in older people living with HIV/AIDS in the state of São Paulo, Brazil - Katyucia Oliveira Crispim de Souza; Ana Clara Cintra Santana; Vinícius do Nascimento Alves; Caíque Jordan Nunes Ribeiro; Allan Dantas dos Santos; Anna Luiza de Fátima Pinho Lins Gryschek (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2023)
ABSTRACT Objective: To analyze the spatiotemporal distribution of mortality in older people living with the human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) in the state of São Paulo, Brazil. Methods: This is an ecological study with temporal and spatial approaches to analyze mortality from HIV/AIDS in the older adult population in the 2010-2020 period in the state of São Paulo, Brazil. Analysis of temporal trends was performed using the joinpoint regression, and spatial analysis was carried out using the Moran's index and the local empirical Bayesian model. Results: We identified a total of 3,070 deaths from HIV/AIDS among older adults and a mortality rate of 51.71 per 100 thousand inhabitants during the study period. The joinpoint method showed a growing trend for the age groups from 70 to 79 years (annual percent change [APC]=3.45; p=0.01) and ≥80 years (APC=6.60; p=0.006) and stability for the general older adult population (APC=0.99; p=0.226). The spatial distribution of the crude mortality rate was diffuse throughout the state. After smoothing by the Bayesian estimator, we observed greater concentration in the eastern mesoregions. In Moran's analysis, we observed clusters of lower mortality rates in more central regions; and of higher rates in the southern and northern regions of the state. Conclusions: We found a major growing trend in mortality from HIV/AIDS in the age group of older adults over 69 years during the 2010-2020 period. Clusters of high mortality rates were located in regions further to the south and north of the state, where places of greater social inequalities are concentrated.